Study on the Effectiveness of Monte Carlo Filtering when Correcting Negative SEA Loss Factors - Paweł Nieradka; Andrzej Dobrucki (Archives of Acoustics, 2023)
The power injection method (PIM) is an experimental method used to identify the statistical energy analysis (SEA) parameters (called loss factors – LFs) of a vibroacoustic system. By definition, LFs are positive real numbers. However, it is not uncommon to obtain negative LFs during experiments, which is considered a measurement error. To date, a recently proposed method, called Monte Carlo filtering (MCF), of correcting negative coupling loss factors (CLFs) has been validated for systems that meet SEA assumptions. In this article, MCF was validated for point connections and in conditions where SEA assumptions are not met (systems with low modal overlap, non-conservative junctions, strong coupling). The effect of removing MCF bias on the results was also examined. During the experiments, it was observed that the bias is inversely proportional to the damping loss factor of the examined subsystems. The obtained results confirm that the PIM, combined with MCF, allows to determine non-negative SEA parameters in all considered cases.